Anti-PD-L1 therapy altered inflammation but not survival in a lethal murine hepatitis virus-1 pneumonia model - Curran, Colleen S.; Cui, Xizhong; Li, Yan; Jeakle, Mark; Sun, Junfeng; Demirkale, Cumhur Y.; Minkove, Samuel; Hoffmann, Victoria; Dhamapurkar, Rhea; Chumbris, Symya; Bolyard, Cameron; Iheanacho, Akunna; et al. (Frontiers in Immunology, 2024)
Because prior immune checkpoint inhibitor (ICI) therapy in cancer patients presenting with COVID-19 may affect outcomes, we investigated the beta-coronavirus, murine hepatitis virus (MHV)-1, in a pneumonia model in the absence (Study-1) or presence of prior programmed cell death ligand-1 (PD-L1) antibody (PD-L1mAb) treatment (Study-2). Study-1 examined physiological, thrombotic, and pro-inflammatory responses 2, 5 and 10 days after infection. Study-1 results recapitulated the pathogenesis of COVID-19 and revealed increased cell surface expression of checkpoint molecules (PD-L1, PD-1), higher expression of the immune activation marker angiotensin converting enzyme (ACE), but reduced detection of the MHV-1 receptor CD66a on immune cells in the lung, liver, and spleen. In Study-2, the effects of PD-L1mAb were evaluated 2 and 5 days after infection, identifying reduced PD-L1 detection on immune cells in the lung, liver, and spleen. PD-L1 blockade was associated with increased cell surface expression of PD-1 and ACE, decreased cell surface detection of CD66a, and improved oxygen saturation despite reduced blood glucose levels and increased signs of tissue hypoxia. In the lung, PD-L1mAb promoted S100A9 but inhibited ACE2 production concomitantly with pAKT activation and reduced FOXO1 levels. PD-L1mAb promoted interferon-γ but inhibited IL-5 and granulocyte-macrophage colony-stimulating factor (GM-CSF) production, contributing to reduced bronchoalveolar lavage levels of eosinophils and neutrophils. In the liver, PD-L1mAb increased viral clearance in association with increased macrophage and lymphocyte recruitment and liver injury. PD-L1mAb increased the production of virally induced mediators of injury, angiogenesis, and neuronal activity that may play role in COVID-19 and ICI-related neurotoxicity. PD-L1mAb did not affect survival in this murine model.